Centro Ecoturístico - Durante, Bruna (2022)
The objective of the present work is to elaborate the architectural project of an Ecotourism Center that offers lodging, gastronomy, adventure, leisure and well-being to the population of Vila Maria and region in order to contribute to the expansion of the scenographic vision of the municipality and to enhance the local infrastructure. The project has a multidisciplinary character as it comprises contact with nature, preservation and environmental education, health, and economic development.